LEVEL OF TACTICAL KNOWLEDGE DECLARED OF YOUNG FEMALE ATHLETES OF THE WEST HANDBALL CUP 2008 (Fiep Bulletin - online, 2013)
The purpose of this study was to identify the level of tactical knowledge-declarative of female athletes in the results of the final round of the West Handball Cup 2008 in relation to the result, sports and made specific experience of players. To that end, there was a descriptive and exploratory research (THOMAS & NELSON, 2002), with 84 female athletes who differed the final step of West Handball Cup 2008, while for data collection using the Test Level of Knowledge Tactical declaratory proposed by Greco et al (2000), and the analysis was used descriptive statistics, specifically, mean and standard deviation, and thereafter the use of non-parametric statistical technique, the Kruskal Wallis test to compare the data. In short it was observed that the tactical thinking, apparently, is not one of the most privileged content in the training sessions of the teams investigated in view that in relation to the competitive result, only in 5 cases (1,3,8,9, and 12) the average levels of tactical declarative knowledge could be considered significant, however, worth emphasizing that many players from teams with the worst record in the competition had high averages in these situations. Moreover, experience in relation to specific sports and posts the average levels of tactical knowledge declaratory could not be considered significant, regardless of the situations analyzed.
Keywords: Tactical Knowledge; Handball; Decision making